Regulation of BOB.1/OBF.1 stability by SIAH - Boehm, Jannic (Oxford University Press, 2001)
The BOB.1/OBF.1 coactivator is critically involved in mediating octamer-dependent transcriptional activity in B lymphocytes. Mice lacking this coactivator show various defects in B-cell development, most notably they completely lack germinal centers. Consistent with this phenotype, BOB.1/OBF.1 levels are massively upregulated in germinal center B cells as compared with resting B cells. We have addressed the mechanism of upregulation and found that only a minor part of this regulation can be attributed to increased levels of BOB.1/OBF.1-specific mRNA. Apparently, BOB.1/OBF.1 is also regulated at the protein level. In support of this suggestion we have been able to identify two related BOB.1/OBF.1 interacting proteins, SIAH1 and SIAH2, in a yeast two-hybrid screen. SIAH1 and SIAH2 are known regulators of protein stability. Cotransfection experiments revealed that coexpression of SIAH results in a destabilization of BOB.1/OBF.1 protein without affecting mRNA levels. Further more, proteasome inhibitors block the degradation of BOB.1/OBF.1 protein. Finally, B-cell receptor cross-linking also resulted in the degradation of BOB.1/OBF.1 and consequently reduced transcriptional activation of BOB.1/OBF.1-dependent reporters.